Membrane support formulation and carrier selection in supported liquid membrane for extraction of zwitterionic form of Glutamic acid - Vikneswary, Rajendaran; Syed M., Saufi; M. A. K. M., Zahari; Abdul Wahab, Mohammad (Elsevier Ltd, 2021)
Glutamic acid (GA) is an amino acid which is usually appear in the zwitterionic form in solutions. At present, cation and anion exchange carriers are widely use to extract this amino acids. However, the carriers only function either at high pH or low pH. Although, the pH can be adjusted by adding certain chemical to reach acidic or basic region, but it may lead to additional byproducts formation and affect the extraction process. In the current study, supported liquid membrane (SLM) was used to extract the zwitterionic form of GA from the aqueous solution without any pH adjustment. In the SLM process, the determination of the best carrier in liquid membrane formulation is important for achieving high extraction of GA. Hence, different types of carriers such as trioctylamine (TOA), tridodecylamin (TDA), tri-n-octyl phosphine oxide (TOPO), mixture of 50% TOA and 50% TDA, aliquat 336 and di-2-ethylhexyl phosphoric acid (D2EHPA) in 2-ethyl-1-hexanol were investigated. The polyethersulfone (PES) membrane with and without graphene membrane supports were prepared, characterized and used as the support in the SLM. The incorporation of graphene in PES membrane had increased the surface contact angle and tensile stress from 80.96 ± 1.92° to 97.8 ± 1.46° and 650.684 kPa to 1079.59 kPa, respectively. Aliquat 336 was identified as the best carrier with 93% of GA extraction.